2017
DOI: 10.1007/s10534-017-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Human topoisomerase inhibition and DNA/BSA binding of Ru(II)–SCAR complexes as potential anticancer candidates for oral application

Abstract: Three ruthenium(II) phosphine/diimine/picolinate complexes were selected aimed at investigating anticancer activity against several cancer cell lines and the capacity of inhibiting the supercoiled DNA relaxation mediated by human topoisomerase IB (Top 1). The structure-lipophilicity relationship in membrane permeability using the Caco-2 cells have also been evaluated in this study. SCAR 5 was found to present 45 times more cytotoxicity against breast cancer cell when compared to cisplatin. SCAR 4 and 5 were bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 59 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…Sk-OV-3 cells, however, were shown to be resistant against both 7-HC and Cisplatin treatment (IC 50 >100 µg/mL). The IC 50 values of Cisplatin on the same cancer cell lines are in agreement with the literature 26,27 . In an attempt to achieve an improved therapeutic outcome, all 4 cell lines were subjected to a combination of 7-HC and the conventional antineoplastic drug Cisplatin (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…Sk-OV-3 cells, however, were shown to be resistant against both 7-HC and Cisplatin treatment (IC 50 >100 µg/mL). The IC 50 values of Cisplatin on the same cancer cell lines are in agreement with the literature 26,27 . In an attempt to achieve an improved therapeutic outcome, all 4 cell lines were subjected to a combination of 7-HC and the conventional antineoplastic drug Cisplatin (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…Herein, we observed that these ruthenium complexes behave like DNA intercalating agents, which can be caused by drug-DNA interactions at the minor groove or/and electrostatic interactions. These effects can occur with octahedral compounds, such as the ruthenium complexes, that are very bulky and that do not intercalate (33, 34). A ruthenium complex containing guanidine has been reported to bind to DNA and induce DNA damage, cell cycle arrest and to activate the typical apoptosis pathways in MCF-7 cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, within the framework of our continuous effort to design novel metallodrug candidates, in the last years, our research group has synthesized several ruthenium complexes with promising pharmacological activities for the anticancer purpose ( 22 26 ). In the light of those findings, herein we have investigated for once the cellular and molecular responses of two novel lapachol-containing ruthenium(II) complexes [Ru(Lap)(dppm)(bipy)]PF 6 ( 1 ) and [Ru(Lap)(dppm)(phen)]PF 6 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%